Postdramatic Theatre and Postdramatic Performance - Marvin Carlson (The City University of New York – New York, United States of America) (Revista Brasileira de Estudos da Presença, 2015)
Beginning with the concept of a postdramatic theatre as articulated by the German theorist Hans-Thies Lehmann, this essay considers the recent work of several major international directors – Ivo van Hove, Punchdrunk, Signa and others – as examples of postdramatic performance. It argues that what they have in common is a challenge to the traditional concept of mimesis and of the theatre world as a fictional construct distinctly separated from everyday life and its surroundings.